Evidence of Histoplasma capsulatum seropositivity and exploration of risk factors for exposure in Busia county, western Kenya: Analysis of the PAZ dataset - Cornell, T.R.; Thomas, Lian F.; Cook, Elizabeth A.J.; Pinchbeck, G.; Bettridge, Judy M.; Gordon, L.; Kivali, Velma; Kiyong'a, Alice; Fèvre, Eric M.; Scantlebury, C.E. (2023)
Background Despite recognition of histoplasmosis as a disease of national public health concern in Kenya, the burden of Histoplasma capsulatum in the general population remains unknown. This study examined the human seroprevalence of anti-Histoplasma antibody and explored associations between seropositivity and demographic and environmental variables, in Busia county, western Kenya.